EVALUASI PELAKSANAAN CLASSROOM ASSESMENT DI MADRASAH TSANAWIAYAH DDI SEPPANGE KECAMATAN BENGO KABUPATEN BONE - St Jumaeda; St Nur Alam (IAIN Ambon, 2020)
Abstract:This study aims to evaluate the implementation of classroom assessment on: (1) aspects of classroom assessment, 2) classroom assessment techniques, and (3) classroom assessment procedures. This research is a survey study, using a formative evaluation model from Michael Scriven.Sampling techniques are purposive samples. The research location is MTs DDI Seppange. Data collection is obtained through questionnaires, interviews, observations, and documentation. Data analysis techniques used are qualitative analysis techniques. The results showed that: (1) classroom assessment techniques carried out by MTS DDI Seppange teachers include written tests, observations, practical tests, assignment assessments, and oral tests, portfolios, journals, peer-to-peer assessment and self-assessment (2) aspects of classroom assessment that have been carried out by teachers covering cognitive, psychomotor, and affective aspects, (3) Classroom assessment procedures that have been carried out by teachers include making question grids, grain analysis , remedial implementation, and follow-up assessment results. The evaluation of aspects, techniques, and class assessment procedures, teachers at MTS DDI Seppange were carried out properly. Keywords: Evaluation, classroom assessment, teachers, Abstrak: Penelitian ini bertujuan untuk mengevaluasi pelaksanaan classroom assessment tentang: (1) aspek-aspek classroom assessment, 2) teknik-teknik classroom assessment, dan (3) prosedur classroom assessment. Penelitian ini adalah penelitian survei, dengan menggunakan model evaluasi formatif dari Michael Scriven.Teknik pengambilan sampel adalah purposive sample. Lokasi penelitian adalah MTs DDI Seppange. Pengumpulan data diperoleh melalui angket, wawancara, observasi, dan dokumentasi. Teknik analisa data yang digunakan adalah teknik analisis kualitatif. Hasil penelitian menunjukkan bahwa: (1) teknik classroom assessment yang dilaksanakan guru MTS DDI Seppange meliputi tes tertulis, observasi, tes praktik, penilaian tugas, dan tes lisan, portofolio, jurnal, penilaian antar teman dan penilaian diri (2) aspek-aspek classroom assessment yang telah dilaksanakan guru meliputi aspek kognitif, psikomotorik, dan aspek afektif, (3) Prosedur classroom assessment yang telah dilaksanakan guru meliputi pembuatan kisi-kisi soal, analisis butir soal, pelaksanaan remedial, dan tindak lanjut hasil penilaian. Hasil evaluasi tentang komponen aspek, teknik,dan prosedur penilaian kelas, guru di MTS DDI Seppange terlaksana dengan baik. Kata kunci: Evaluasi, penilaian kelas, guru,